ONE HUNDRED YEARS OF THE ANC: DEBATING LIBERATION HISTORIES TODAY - Visser, Deon (Scientia Militaria - South African Journal of Military Studies, 2015)
One hundred years of the ANC comprises a selection of papers by South African and international scholars read at a conference titled “One Hundred Years of the ANC: Debating Liberation Histories and Democracy Today” held at the University of the Witwatersrand in Johannesburg from 20 to 23 September 2011. The book commences with the two keynote addresses that framed the academic debate at the above-mentioned conference. The first, by Philip Bonner, addresses the topic “Fragmentation and cohesion in the ANC: The first 70 years”. The second one, contributed by Joel Netshitenzhe, is entitled “A continuing search for identity: Carrying the burden of history”. These keynote addresses are followed by an introductory chapter by the first three editors of the book and fourteen chronologically arranged chapters on various aspects of the ANC’s hundred-year history.